Design Layout and Circulation Design of Type A Passenger Terminal in Kota Singkawang - Adna, Serafina Gebria; Said, Said; Mukti, Elsa Tri (Fakultas Teknik Universitas Tanjungpura, 2024)
Kota Singkawang, located in Kalimantan Barat Province, is a popular destination for domestic and international visitors. According to the 2013